Some relational theories on the structure of space-time: physics, philosophy, theology - Lorente Páramo, Miguel (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
We present some modern theories on the structure of space-time that can be classified as relational theories in the direction of Leibniz’s ontology. In particular we summarize the Leibniz’s position against Newton and Clarke on the nature of space-time, Penrose’s model of spin networks, Heisenberg’s fundamental equation for the unification of elementary particles, Finkelstein’s space-time code, Weizsäcker’s urs theory that unifies the postulates of quantum mechanics and the theory of relativity, Sorkin’s causal sets, Markopoulou’s quantum causal histories, Markopoulou and Smolin’s causal spin foams, in the last three of which the principle of causality has been introduced. In order to analyze the nature of space-time, we consider three levels of knowledge —observational, theoretical and ontological— to which the different models can be ascribed. Following similar approach to the models mentioned in the first sections, we present our theoretical model of the structure of the space-time, some physical applications and the ontological interpretation of the model. In order to implement the above models with theological aspects we present in the last sections two theologians, Pannenberg and Torrance, who have made explicit analysis of the nature of space-time from a relational point of view. Following their expositions we have presented, after some epistemological presuppositions, the connection between the Creation and the rationality of God through the structure of space-time and the communication of God to the creatures in the Incarnation through the same structure.
Keywords: space-time; relational theory; spin networks; urs theory; space-time code; causal sets; spin foams; quantum causal histories; causal cubic lattice; Creation; God rationality; Incarnation